2014
DOI: 10.1037/a0035422
|View full text |Cite
|
Sign up to set email alerts
|

Emotion reactivity and regulation are associated with psychological functioning following the 2011 earthquake, tsunami, and nuclear crisis in Japan.

Abstract: Frequent and successful use of cognitive reappraisal, an emotion regulation strategy that involves rethinking the meaning of an emotional event in order to change one's emotional response, has been linked in everyday life to positive outcomes such as higher well-being. Whether we should expect this association to be maintained in a strong, temporally and spatially close emotional context is an unexplored question that might have important implications for our understanding of emotion regulation and its relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…As during the diagnosis session (Time 1), participants' depressive symptoms were assessed with the M=14.20,SD=15.08), with the suicidal ideation item excluded (see Cavanagh et al, 2014;Wisco and Nolen-Hoeksema, 2009 for a similar approach).…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…As during the diagnosis session (Time 1), participants' depressive symptoms were assessed with the M=14.20,SD=15.08), with the suicidal ideation item excluded (see Cavanagh et al, 2014;Wisco and Nolen-Hoeksema, 2009 for a similar approach).…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…It was initially diagnosed among veterans of the Vietnam War. Subsequent studies indicated that victims of disasters were also potentially suffering from PTSD (Cavanagh et al, 2014). It has been calculated that life time prevalence of PTSD in adults is 7.8%, while women have higher risk than men (20.4 vs. 8.2%) despite experiencing fewer traumas (Kessler et al, 2005; Ditlevsen and Elklit, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) may develop after a person is exposed to a traumatic event, characterized by repeatedly experiencing trauma with disturbing recurring flashbacks, avoidance or numbing of memories of the event, and hyper-arousal 1 4 . It was first recognized as a distinct disease among US-American Vietnam veterans and becomes popular due to high prevalence, strong psychological upset and difficult prediction.…”
Section: Introductionmentioning
confidence: 99%